Non-classical pulmonary exacerbation in cystic fibrosis revealing ALK-Translocated lung cancer: A case report - Mohamad Hadhud; Johnathan Arnon; Anat Hershko-Moshe; Adi Hollander; Noa Hurvitz-Lehmann; Assaf Potruch; Henny Azmanov; Rottem Kuint; Nurith Hiller; Elie Picard; Naama Sebbag-Sznajder; Shira Leebhoff; et al. (Respiratory Medicine Case Reports)
Lung cancer is uncommon among people with cystic fibrosis (pwCF). We describe the case of a 35-year-old man with mild, stable CF disease who presented with severe respiratory distress, systemic symptoms, elevated liver enzymes and hypereosinophilia along with a lung mass and pleural effusion. The patient was subsequently diagnosed with non-small cell lung carcinoma (NSCLC), featuring anaplastic lymphoma kinase (ALK) translocation. Following treatment with a targeted tyrosine kinase inhibitor (TKI) there was a rapid tumor regression, however, his dyspnea and hypoxemia subsequently worsened. A trial of Elexacaftor/Tezacaftor/Ivacaftor (ETI) led to significant clinical improvement and enhanced pulmonary function. In vitro testing using patient-derived intestinal organoids was performed in parallel and also demonstrated a significant response to ETI. The deterioration observed following the initiation of ALK inhibitor treatment and subsequent improvement with CFTR modulators suggest that ALK inhibitor therapy may potentially impair CFTR activity. A better understanding of the relationship between these pathways could provide valuable insights and contribute to the development of more effective and tailored treatment strategies for patients with coexisting conditions. To our knowledge, this is the first reported case of ALK-translocated lung cancer in a CF patient, underscoring the necessity for a high degree of clinical suspicion in atypical presentations of pulmonary exacerbation and potentially linking ALK-EML4 activation pathways, TKI therapy and CFTR. Care for pwCF with lung cancer requires a unique multi-disciplinary approach to optimize their complex multifactorial treatment.